Carfilzomib: A Promising Proteasome Inhibitor for the Treatment of Relapsed and Refractory Multiple Myeloma - Jayaweera, Shansa Pranami E.; Wanigasinghe Kanakanamge, Sacheela Prasadi; Rajalingam, Dharshika; Silva, Gayathri N. (Frontiers in Oncology, 2021)
The proteasome is crucial for the degradation of intracellular proteins and plays an important role in mediating a number of cell survival and progression events by controlling the levels of key regulatory proteins such as cyclins and caspases in both normal and tumor cells. However, compared to normal cells, cancer cells are more dependent on the ubiquitin-proteasome pathway (UPP) due to the accumulation of proteins in response to uncontrolled gene transcription, allowing proteasome to become a potent therapeutic target for human cancers such as multiple myeloma (MM). Up to date, three proteasome inhibitors namely bortezomib (2003), carfilzomib (2012), and ixazomib (2015) have been approved by the US Food and Drug Administration (FDA) for the treatment of patients with relapsed and/or refractory MM. This review mainly focuses on the biochemical properties, mechanism of action, toxicity profile, and pivotal clinical trials related to carfilzomib, a second-generation proteasome inhibitor that binds irreversibly with proteasome to overcome the major toxicities and resistance associated with bortezomib.